THE PREVALENCE OF EIMERIA SPP. INFECTION ON DOMESTIC CHICKEN IN BALI - Billa, Ayu Talia Shalsa; Dwinata, I Made; Oka, Ida Bagus Made (Buletin Veteriner Udayana; Vol. 15 No. 6 December 2023DO - 10.24843/bulvet.2023.v15.i06.p21, 2023)
Domestic chickens are widely raised by people in Bali with a semi-intensive and traditional maintenance system so that the health of the chickens is not considered. One of the parasitic diseases that poultry farmers often face is coccidiosis or blood in stool that caused by the protozoan parasites of the gastrointesinal tract of the genus Eimeria parasitic infection. The purpose of this research was to determine the prevalence of Eimeria sp p. infection on domestic chickens in Bali as well as the correlation between male and female sex and regional location to the prevalence of Eimeria spp. infection on domestic chickens in Bali. Sampling was carried out by purposive sampling in several areas in Bali, namely Badung, Gianyar, Tabanan, and Denpasar City. The object of the research used was domestic chickens aged 5-6 months as many as 100. Stool samples are taken directly after defecation and then placed in a sample pot, then 2% solution of potassium bichromate (K 2 Cr 2 O 7 ) is added which serves as a fertilizing agent for the Eimeria spp. oocyst. Examination of fecal samples using the floating method with saturated NaCl. The results showed that the prevalence of Eimeria spp. infection on domestic chickens in Bali was 51%. After analyzing the data by using chi-square test, it was stated that the male and female sex and location of the sampling area were not related to the prevalence of Eimeria spp. infection in domestic chickens in Bali. Given the high prevalence of Eimeria spp. infection on domestic chicken in Bali, it is recommended to the farmers of domestic chicken in Bali to further improve the husbandary management.